2007
DOI: 10.1108/14777830710731798
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of improved stoves and deforestation in Zanzibar

Abstract: Purpose -The study is specifically aimed at understanding the extent of fuel wood consumption for cooking and the adoption of improved charcoal stoves as a policy option toward reducing the consumption of fuel wood in urban sectors. Design/methodology/approach -Both primary and secondary data were used. Primary data were collected by use of structured questionnaires, interviews and direct field observation. The statistical package for social sciences (SPSS) was used to analyze data. Based on the research plan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Previous studies have demonstrated that education about the detrimental impacts of household air pollution, combined with marketing and availability foster behavior change [ 18 , 28 , 29 , 47 , 51 ]. Further research is necessary to understand the known and perceived risk of household air pollution among traditional stove users.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that education about the detrimental impacts of household air pollution, combined with marketing and availability foster behavior change [ 18 , 28 , 29 , 47 , 51 ]. Further research is necessary to understand the known and perceived risk of household air pollution among traditional stove users.…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, one study found that socioeconomic level was positively correlated with improved cookstove adoption [ 30 ]. A study in Tanzania found that cost was a barrier in the adoption of improved stove technologies [ 29 ]. Therefore, although cost was not a factor of this study, data are consistent with previous research implying that wealth impacts the quality of stoves that households utilize.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation process introduced the theoretical functioning as well as practical knowledge of ICS construction. The provision of this information, including that of ICS efficiency, as well as its economic and environmental benefits, to community members was designed to strengthen the community and to ease diffusion and adoption (Omar Makame 2007).…”
Section: Implementation Strategy and Participatory Knowledge Exchangementioning
confidence: 99%
“…The change would be non-trivial. Innovations that reduce the consumption of wood fuel can contribute to the preservation of the environment and health (Abdelnour and Branzai, 2010;Makame, 2007).…”
Section: Appendix Case A: Fuel Efficient Stovesmentioning
confidence: 99%